Analisis Determinan Faktor Lingkungan Fisik terhadap Upaya Pencegahan Penyakit Akibat Kerja (PAK) di Industri Papan Semen Cor - Purnaning Wahyu Prabarini; Amira Putri Handini; Febri Endra Budi Setyawan; Feny Tunjungsari (ARTERI : Jurnal Ilmu Kesehatan, 2022)
Occupational diseases still contribute to high mortality rates. Physical environment will always be encountered by workers so the risk of exposure will be higher. Physical Environment hazard can cause occupational disease due to work and affect losses both workers and company seriously. The purpose of this study is to analyze correlation between the determinants of physical environment factor with the efforts to prevent occupational disease in the Cast Cement Board Industry, Malang Regency.Observasional-analytic with cross-sectional method was conducted to determine the association between determinants of physical environment factors with the efforts to prevent occupational disease in the Cast Cement Board Industry, Malang Regency. A total sample size of 188 workers were included in this study. Data collection was done directly through questionnaires. To process the data, SEM-PLS (Structural Equation Modelling - Partial Least Square) analysis was conducted.The result showed that there was an correlation between physical environment factors in workers with the efforts to prevent occupational disease (P= 2,683, P>1,96) and there was also a significant correlation between noise (P= 6,029, P> 1,96) and climate (P=4,592, P> 1,96) with the efforts to prevent occupational disease.This study concludes that there is a significant relationship between physical environment factors with the efforts to prevent occupational disease.